Hubungan Metode Pembelajaran Diskusi Buzz Group dengan Aktivitas Belajar Siswa pada Mata Pelajaran IPS Terpadu - Deliana Nifu; Hadi Gunawan Sakti (UNDIKMA, 2020)
The purpose of this study was to determine the relationship between the buzz group discussion learning method with student learning activities in Integrated Social Studies subjects Class VIII at SMPN 4 Praya Barat Daya. The method used in this research is correlational with a questionnaire as the main method, observation and documentation as a complementary method. This study took a sample of class VIII students. B at SMPN 4 Praya Barat Daya, Central Lombok. The data analysis in this study used a quantitative approach using the Moment Product Correlation. Based on the results of data analysis, the correlation coefficient was found to be 0.405. Based on N = 14 with a significance level of 5% r table of 0.553. This means that rtabel is greater than rcount, namely 0.553> 0.405, so it can be concluded that there is a relationship between the Buzz Group discussion learning method and student learning activities in integrated social studies subjects Class VIII at SMPN 4 Praya Barat.